Business transformation processes and Society 5.0: Opportunities and challenges - Silva, D.; Ferreira, F.; Milici, A.; Ferreira, J.; Ferreira, N. (Management Decision, 2026)
Purpose In light of the challenges and opportunities posed by globalization and technological advancements, this study aims to develop a decision-support system to assist companies in identifying, structuring and prioritizing variables influencing their transformation and adaptation processes to Society 5.0. Design/methodology/approach The research employs a methodological approach focused on knowledge creation through expert discussions involving diverse backgrounds. Cognitive mapping and interpretive structural modeling (ISM) guide the process, allowing for the integration of subjective elements into the analysis system while ensuring objectivity through ISM. The methodology involves structuring the decision problem, identifying and ranking key factors and evaluating their cause-and-effect relationships. Findings The analysis underscores the significance of technology and external factors compared to other areas of interest within the model. Consequently, the study emphasizes the necessity for companies to pay special attention to these types of factors during their transformation processes. Research limitations/implications While the study provides valuable insights, the reliance on expert discussions may introduce biases or overlook certain perspectives. Additionally, the findings may not be universally applicable and may require customization based on specific organizational contexts or industries. However, the proposed decision-support system offers a practical tool for companies seeking successful adaptation to Society 5.0. Originality/value This study provides a novel approach to addressing the challenges posed by globalization and technological advancements. It presents a valuable resource for organizations striving to adapt effectively in the evolving socioeconomic landscape.